Modelagem e análise de vulnerabilidade de aquíferos: um estudo de caso do município de Lajeado-RS - (:unkn) unknown (Universidade Federal do Pampa, 2021)
With potential sources of contamination mainly in urban areas, aquifers overlying these zones are more vulnerable to contamination. Based on the relevance of the economic and sustainable use of water sources, particularly underground, this work proposes the modeling of quantitative and qualitative parameters related to underground aquifers, to estimate the degree of natural vulnerability of the Serra Geral and Guarani aquifers, in portion superimposed on the municipality of Lajeado - RS. The assessment of the natural vulnerability of aquifers is an extremely important study to recognize areas that may be subject to contamination. For this, a database with quantitative parameters was consolidated, establishing the aquifer quotas, determining the potential sources of contamination that may be present in the study area, analyzing parameters for recognition and determination of aquifer vulnerability, using the DRASTIC and GOD methods, generating aquifer vulnerability maps in the studied area. With the help of the Surfer software, it was possible to generate maps of aquifer vulnerability indices, location maps, compare methods and assess vulnerability. With the case study, it can be observed the occurrence of few places where there is high vulnerability, demonstrated only in the DRASTIC method, being restricted to places where there is little or no aquifer coverage. From the comparison of the general results obtained in each method, it can be noted that, depending on the method adopted, the vulnerability class may change, as the influence of each parameter as well as the weight adopted changes according to the method.
Keywords: Aquífero Serra Geral; Aquífero Guarani; Modelagem espacial; DRASTIC; GOD; Serra Geral Aquifer; Guarani Aquifer; Spatial modeling; CNPQ::CIENCIAS EXATAS E DA TERRA